Mainstream teachers views about including children with special needs into regular classrooms - Nonis, Karen (CIP- Anadolu Universitesi, 2008)
The Special Education scene is changing rapidly in Singapore. More and more, we are seeing and increasing number of children with special needs being included in regular classrooms. Since early 2005, the Singapore Government has invested large sums of money in recruiting and training what is called Special Education Officers to assist teachers who have children with special needs in their classrooms. To further enhance this support for children with special needs in regular classrooms, the Ministry of Education (MOE) together with the National Institute of Education (NIE) provides additional special needs training to already qualified teachers in regular classrooms. these trained teachers undergo what is called a TSN course (Teachers' Trained in Special Needs) at the NIE which is the main training arm of the MOE. Courses are also offered as core or elective course course to all mainstream teachers undergoing pre-service teacher training at the NIE. With the current developments in special education, it is important to know that teacher's feel about including children with special needs into their classroom and their concerns.